Hearing in color: How expectations distort perception of skin tone. - Lyngs, U; Cohen, E; Hattori, W; Newson, M; Levin, D (American Psychological Association, 2016)
Previous research has found that the perceived brightness of a face can be distorted by the social category of race. Thus, Levin and Banaji (2006) found, in a U.S. sample, that faces of identical brightness were perceived to be lighter if they had stereotypical White American features than if they had Black American features. Here, we present 2 experiments conducted in Natal, Brazil, that extend this line of research. Experiment 1 tested if the brightness distortion effect would generalize to a Brazilian population. Experiment 2 tested if speech accent would have a similar effect on brightness perception. In Experiment 1, we found that the brightness distortion effect clearly replicated in the Brazilian sample: Faces with Black racial features were perceived to be darker than faces with White racial features, even though their objective brightness was identical. In Experiment 2, we found that speech accent influenced brightness perception in a similar manner: Faces were perceived to be darker when paired with an accent associated with low socioeconomic status than when they were paired with an accent associated with high socioeconomic status. Whereas racial concepts in Brazil are often claimed to be much more fluid compared with the United States, our findings suggest that the populations are quite similar with respect to associations between facial features and skin tone. Our findings also demonstrate speech accent as an additional source of category information that perceptual cognition can take into account when modeling the world.